2015
DOI: 10.1017/s0954394515000071
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on ellipsis alternation: A view from the history of English

Abstract: I offer a diachronic perspective on English ellipsis alternation, or the alternation between inclusion and omission of prepositions from remnants under sluicing and bare argument ellipsis. The relative freedom to omit prepositions from remnants has not been stable in English; this freedom is connected to the strength of semantic dependencies between prepositions and verbs. Remnants without prepositions are first attested, but remain less frequent than remnants with prepositions, as late as Early Modern English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…E&F present no actual historical data in this section; however, in Nykiel's (2015) study of the diachrony of sluicing in English, she finds no examples of preposition omission under sluicing from the Middle English period, as opposed to twenty-three examples in which the preposition is overt, such as (13). Apparently, the split infinitive has a somewhat unstable history in English.…”
Section: Exemption Of the Preposition From Sluicingmentioning
confidence: 80%
“…E&F present no actual historical data in this section; however, in Nykiel's (2015) study of the diachrony of sluicing in English, she finds no examples of preposition omission under sluicing from the Middle English period, as opposed to twenty-three examples in which the preposition is overt, such as (13). Apparently, the split infinitive has a somewhat unstable history in English.…”
Section: Exemption Of the Preposition From Sluicingmentioning
confidence: 80%
“…There is evidence that mismatch in such content degrades the acceptability of sluicing, whether or not ellipsis alternation is involved, as in (12)-(13) (Dayal & Schwarzschild 2010;Nykiel 2013b Further, independent evidence shows that matching contentful correlates and remnants (lexical NPs and which-NP phrases) are found more acceptable than matching noncontentful ones (indefinite pronouns and bare wh-phrases) in English sluicing with appositive antecedents, as in 14 If the acceptability contrast between contentful and noncontentful correlates and remnants is a general characteristic of sluicing, it is not surprising to find it in ellipsis alternation. In fact, this contrast has been reported in ellipsis alternation beyond Spanish: French, Serbo-Croatian, Polish, Czech, Russian, and Early and Late Modern English (Stjepanović 2008;Szczegielniak 2008;Rodrigues et al 2009;Caha 2011;Sag & Nykiel 2011;Nykiel 2013aNykiel , 2015Tatiana Philippova p.c.). 3 This list suggests that a larger generalization can be made about why ellipsis alternation is not merely a characteristic of preposition-stranding languages.…”
Section: Semantic and Syntactic Content Of The Remnant And Correlatementioning
confidence: 96%
“…When the fragment's correlate hosts a lexical NP, and not a pronoun, that fragment is more likely to surface as an NP than a PP (Nykiel, 2015(Nykiel, , 2017, hence (21B) is more probable than To who(m). This preference for lexical NP antecedents over indefinite pronouns with NP fragments has been reported in several cross-linguistic studies of clausal ellipsis (see Caha, 2011, for Czech;Rodrigues et al, 2009, for Brazilian Portuguese, Spanish, and French;Stjepanovic, 2008, for Serbo-Croatian;Szczegielniak, 2008;Sag & Nykiel, 2011;Nykiel, 2013, for Polish).…”
Section: M I F a N D E N V I R O N M E N T S F A C I L I T A T I mentioning
confidence: 99%
“…An interesting further aspect of this development is that the frequency of prepositional verbs more than doubles after Early Modern English (Biber, Johannsson, Leech, Conrad, & Finegan, 1999). It is also after this period that the proportion of NP fragments to PP fragments under ellipsis rises (Nykiel, 2014(Nykiel, , 2015, setting Modern English apart from earlier English and from so many other languages as well. 12 The explanatory question this raises is: Can it be shown that the much larger number of semantic dependencies now holding between verbs and prepositions is actually responsible for more NP fragments in present-day English?…”
Section: Predictions Of Mid F or English P-dropmentioning
confidence: 99%
See 1 more Smart Citation